Cerebral Infarction in Immune Thrombotic Thrombocytopenic Purpura Is Associated with Old Age, Hypertension, Smoking, and Anti-ADAMTS13 Ig, But Not with Mortality - Memon, Raima; Sui, Jingrui; Lin, Chen; Zheng, X. Long (TH Open, 2021)
Background Neurological involvement is common in patients with immune thrombotic thrombocytopenic purpura (iTTP), but the frequency, risk factors, and outcomes of these with imaging-confirmed stroke in iTTP are not known.Methods We selected 66 out of 109 iTTP patients with neurological signs and symptoms and reviewed their CT/MRI (computed tomography/magnetic resonance imaging) findings for the evidence of stroke and other clinical information in Alabama TTP Registry.Results Of these, 52 (78.8%) had their CT/MRI done on admission in whom 22 (42.3%) were positive for multiple acute or chronic infarcts. The patients with image-confirmed ischemic stroke were older, and appeared to be associated with a history of hypertension and smoking. Additionally, patients with imaging-confirmed stroke showed higher plasma concentrations of anti-ADAMTS13 IgG than those without stroke. More interestingly, there was no statistically significant difference in the rate of exacerbation and 60-day mortality between those with and without stroke.Conclusion Ischemic cerebral infarcts are common findings in brain imaging studies of patients with acute iTTP; old age, chronic hypertension, and smoking, as well as high plasma concentrations of anti-ADAMTS13 IgG may be the potential risk factors for cerebral infarction in these patients. The presence of image-confirmed ischemic stroke, however, does not predict exacerbation and 60-day mortality, although the long-term effect of such ischemic brain damage on cognitive function and quality of life remains to be determined.
Keywords: thrombotic thrombocytopenic purpura; inflammatory mediators; ADAMS/ADAMTS13; von Willebrand factor; cerebrovascular disease; autoimmune diseases; autoantibodies